ENHANCING BIOPHYSICS EDUCATION THROUGH AN INTEGRATIVE METHODOLOGICAL APPROACH (Ta'limning zamonaviy transformatsiyasi, 2024)
Biophysics, a multidisciplinary field at the intersection of biology and physics, is essential for understanding the fundamental principles governing living systems. However, teaching biophysics effectively presents challenges due to its diverse nature and the need for students to grasp concepts from both biological and physical sciences. In this article, we propose an integrative methodological approach to enhance the teaching of biophysics. This approach aims to bridge the gap between biology and physics by integrating concepts, theories, and experimental techniques from both disciplines. By providing a holistic view of biophysical phenomena, students can develop a deeper understanding of complex biological systems and their underlying physical principles. We discuss various strategies and pedagogical tools that can be employed to implement this approach in the classroom, including interdisciplinary projects, hands-on experiments, and computational modeling. Furthermore, we highlight the benefits of adopting an integrative approach for both students and educators, such as fostering critical thinking skills, promoting interdisciplinary collaboration, and preparing students for careers in biophysics research and beyond. Overall, we argue that an integrative methodological approach holds great promise for improving the teaching and learning of biophysics, ultimately contributing to the advancement of this vital field.